Rethinking planning hierarchy considering climate change as global catastrophe - Mattia Bertin; Francesco Musco; Lorenzo Fabian (Climate Risk Management, 2020)
This article proposes overcoming the distinction between the effects of climate change and the effects linked to classical disaster hazards by considering Climate Change as global catastrophe. The theoretical approach to combining the two models has until now greatly emphasized the need for further research, but with poor results. Starting from a new conception of climate change as a catastrophe in progress, the paper proposes a revision of local planning hierarchy in order to give a primary role to risk assessment in every sector of local development.